The Role of Innovation Capability and Human Resource Management in Realizing Competitive Advantage: Case Study at Angliss Bakehouse Medan City - Fernando Capreli; Lisa Elianti Nasution (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This research aims to analyze the role of innovation capability and human resource management in realizing Angliss Bakehouse's competitive advantage in Medan City. The quantitative research method with the Structural Equation Modeling approach based on Partial Least Squares (SEM-PLS) was applied to 100 consumer respondents through incidental sampling techniques. The results of the analysis showed that innovation capability had a positive and significant effect on competitive advantage with a path coefficient of 0.335 (p=0.021) and an effect size of f² of 0.143, although it was relatively weak. Meanwhile, human resource management exerted a stronger influence with a path coefficient of 0.554 (p < 0.001) and f² of 0.390. The two variables together explain the 71.7 % variation in competitive advantage (R²=0.717, Q²=0.677), confirming the model's predictive relevance. These findings indicate that innovation needs to be supported by effective HR practices for the consistent implementation of new ideas. The practical implications of this research prompted Angliss Bakehouse to strengthen its R&D team, develop structured training modules, and integrate R&D and HR functions. In addition, the digitization of operational and marketing processes, as well as the implementation of an open innovation framework are proposed as strategies to strengthen the competitive base and encourage sustainable business growth.